Improving the strategic provisions of the state policy on the development of physical culture and sports in the higher education system - Svirko, Svitlana; Odnovorchenko, Ihor (Public Policy and Accounting, 2024)
The article examines the strategic provisions of state policy on the development of physical culture and sports in the higher education system. Based on the analysis of the Strategy for the Development of Physical Culture and Sports until 2028, the Strategy for the Development of Higher Education in Ukraine for 2022-2032, as well as a critical analysis of the Recommendations for the Strategic Development of Physical Education and Sports among Students until 2025, highly problematic positions of the latter document were identified in terms of digital materials, goals, components, objectives, directions, and expected results. To overcome the identified problems, the following architectonics of the draft Strategy for the Development of Physical Culture and Sports in Ukrainian Higher Education Institutions was proposed and justified: base, analytical, problem, target, and supply clusters, as well as strategic goals for the future document. Implementing this proposed architectonics, along with the substantive target content developed, will lead to tangible results in the development of physical culture and sports in the educational space of domestic higher education. This, in turn, will contribute to strengthening the statehood and resilience of our country.